Rapid prototyping in traditional decorative metallic pewter parts - J. Lino (2009)
In Portugal there a large number of traditional SMEs, operating in different industrial sectors, that still did not awake for the new reality of global competition, where the capacity to develop new products in short periods of time is fundamental to survive in such an aggressive market. Consumers are continuously pressing enterprises for more reliable and sophisticated products that incorporate new materials, new functionalities, and simultaneously have shorter life cycles. These new challenges demand capacities to internally develop new products using digital modelling, rapid prototyping, conversion technologies, rapid manufacturing and others tools that are already common in industrial sectors such as aeronautics, automotive, medical, house appliances, toys and others. In this communication the authors present how the adoption of these technologies were fundamental to rapidly create new products in a traditional manufacturing pewter company that still has an intensive human labour and traditional way for product development, and how these new methodologies were fundamental to quickly manufacture, by centrifugal and conventional casting, spinning and sheet metal forming, and introduce, with success, these products in the international market.